2022
DOI: 10.3390/ijerph19159076
|View full text |Cite
|
Sign up to set email alerts
|

Social Life of Females with Persistent COVID-19 Symptoms: A Qualitative Study

Abstract: Persistent COVID-19 symptoms (long COVID) may bring challenges to long haulers’ social lives. Females may endure more profound impacts given their special social roles and existing structural inequality. This study explores the effects of long COVID on the social life of female long haulers. We conducted semi-structured interviews via Zoom between April and June 2021 with 15 female long haulers in the United States, purposely recruited from Facebook and Slack groups and organization websites related to long CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 73 publications
1
37
0
Order By: Relevance
“…Specifically, social risk factors reduced the ability to maintain a healthy lifestyle, limit sources of psychological stress, and pursue clinical care. In another study by Aghaei, Zhang, et al (2022), American women expressed how their recovery was impeded by employment‐related challenges, an inability to pay medical bills, and a lack of health insurance. Beyond interfering with healthcare visits, there is a wealth of data on the biological implications of social risk factors, termed social determinants of health (Marmot & Wilkinson, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, social risk factors reduced the ability to maintain a healthy lifestyle, limit sources of psychological stress, and pursue clinical care. In another study by Aghaei, Zhang, et al (2022), American women expressed how their recovery was impeded by employment‐related challenges, an inability to pay medical bills, and a lack of health insurance. Beyond interfering with healthcare visits, there is a wealth of data on the biological implications of social risk factors, termed social determinants of health (Marmot & Wilkinson, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…We gathered information on the influence of persistent COVID-19 symptoms on female-long-haulers' lives and the coping strategies utilized by them. The interview guide (see Supplementary Data 1), developed for a larger study, investigates different aspects of long COVID and lived experiences of female long haulers (50). The open-ended interview questions were derived based on the literature to find To compensate for the time of participants, we gave a $30 Amazon e-gift card to each participant.…”
Section: Data Collectionmentioning
confidence: 99%
“…Early qualitative research on the broader patient experience of COVID-19 has revealed some common themes including symptom variability, a heavy sense of stigma, siloed care, the burden on patients to access care, and fear of a permanent reduction in physical and cognitive abilities [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. Open-ended survey studies have also highlighted themes such as multiple symptoms with variable intensity, challenges seeking medical care, motivation to move forward with self-compassion, and also interest in participating in research to explore more about the condition [ 10 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%